2016
DOI: 10.1002/biof.1278
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin during lactation reduces lipopolysaccharide‐induced brain injury

Abstract: Lactoferrin (Lf), component of maternal milk, has antioxidant, anti‐inflammatory and antimicrobial properties. Neuroprotective effects of Lf on the immature brain have been recently shown in rodent models of intrauterine growth restriction and cerebral hypoxia/ischemia. Here we postulated that Lf could also have beneficial effects on preterm inflammatory brain injury. Lf was supplemented in maternal food during lactation and lipopolysaccharide (LPS) was injected in subcortical white matter of rat pups at postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 74 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…In this context, we have shown that lactoferrin (LF), an iron-binding glycoprotein member of the transferrin family found in secretions (for review, see [36]), is a promising strategy for protecting the developing brain against injuries. LF is the main whey protein in breast milk [37][38][39] and its biological properties decrease HI and inflammation-induced brain damage [40,41] and reverse maturational delays following intrauterine growth restriction (IUGR) [42,43] through antioxidative, anti-inflammatory and neurotrophic properties. LF has been shown to protect the developing brain against HI damage in a dose response manner [44].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have shown that lactoferrin (LF), an iron-binding glycoprotein member of the transferrin family found in secretions (for review, see [36]), is a promising strategy for protecting the developing brain against injuries. LF is the main whey protein in breast milk [37][38][39] and its biological properties decrease HI and inflammation-induced brain damage [40,41] and reverse maturational delays following intrauterine growth restriction (IUGR) [42,43] through antioxidative, anti-inflammatory and neurotrophic properties. LF has been shown to protect the developing brain against HI damage in a dose response manner [44].…”
Section: Introductionmentioning
confidence: 99%